Clinical significance of neonatal menstruation. (January 2016) - Brosens, Ivo; Benagiano, Giuseppe
Abstract: Past studies have clearly shown the existence of a spectrum of endometrial progesterone responses in neonatal endometrium, varying from proliferation to full decidualization with menstrual-like shedding. The bleedings represent, similar to what occurs in adult menstruation, a progesterone withdrawal bleeding. Today, the bleeding is completely neglected and considered an uneventful episode of no clinical significance. Yet clinical studies have linked the risk of bleeding to a series of events indicating fetal distress. The potential link between the progesterone response and major adolescent disorders requires to be investigated by prospective studies.